The Challenges Of Submitting Students' Project Through Google Classroom In PostPandemic - Adiatya, Salwa; Ulya, Inayatul (LPPM Universitas Pekalongan, 2024)
This study was aimed to describe the strength and weaknesses of implementation Google Classroom as a platform to submit students’ project in post-pandemic. This research was conducted at SMAN 1 Wiradesa in the eleventh graders. This study used a descriptive qualitative methodology. To know the strength and weaknesses of implementation Google Classroom as a platform to submit student’s project in postpandemic, the researcher conducted interviews with English teacher and gave questionnaires to class XI MIPA 1 SMAN 1 Wiradesa. The result showed that Google Classroom makes it easier for students and teachers. The accessibility of materials, assignments, and student collections is facilitated in part by Google Classroom. Students are reminded when it is time to turn in their assignments, and they can also ask with their teachers in person if they have any questions. Because it can be done from any location at any time, using Google Classroom as a platform for assignment submission helps both students and teachers. The Google Classroom menus assist teacher and students in the learning process so that it can be collected in real time. The weakness is the problem of network connection, a weak network connection will take a long time to download and submit assignments. This is what sometimes makes students late in submitting assignments. The second, there is a deadline for submitting assignments. due to the large number of assignments that students have from various subjects. It makes the students late in submitting assignments. The third is internet quota. many students have limited internet quota and only a few students have wifi at their homes. Key words : Google Classroom, students’ project